(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to develop Google Classroom-Based Online Learning Media in Christian Spirituality Course. The respondents in this study were lecturers of Christian spiritual courses at the Faculty of Christian Education, Tarutung State Institute for Christian Studies and third semester students of the Christian Education Management Department. The research instrument used is a questionnaire (questionnaire). The research method used in this study is Research and Development (R&D), using Borg and Gall using 5 steps. Validation instruments are given to validators and limited trials are carried out to students, then data is collected and analyzed. Based on the results of data analysis of the assessment of four experts as follows: the results of design expert validation are 80.95% in the category of quite feasible to use, then the results of material experts are 88.49% in the category of very feasible to use. Then the results of the trial analysis were limited to students obtained the following results: One-on-one evaluation results of 84.17% are in the category of quite feasible. Then the small group results of 86.34% were in the very feasible category and the results of large group trials of 88.17% were in the very feasible category. Thus based on these percentages, the Google Classroom Learning Media developed is in the category of very feasible to use. This means that Google Classroom is declared to still be used as a face-to-face learning medium.